2015
DOI: 10.1097/nmd.0000000000000261
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations Between Interpersonal Relationship Functioning and Mood Episode Severity in Youth With Bipolar Disorder

Abstract: This study examined the longitudinal association between mood episode severity and relationships in BP youth. Participants were 413 Course and Outcome of Bipolar Youth study youth, aged 12.6 ± 3.3 years. Monthly ratings of relationships (parents, siblings, and friends) and mood episode severity were assessed by the Adolescent Longitudinal Interval Follow-Up Evaluation (ALIFE) Psychosocial Functioning Schedule (PFS) and Psychiatric Rating Scales (PSR) on average every 8.2 months over 5.1 years. Correlations exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Findings add to the literature on familial processes in childhood-onset BD and suggest that family functioning deficits are robust and salient into young adulthood (Belardinelli et al, 2008; Keenan-Miller et al, 2012; Nader et al, 2013; Perez Algorta et al, 2017; Schenkel et al, 2008). This is important and concerning, as family factors are associated with onset and worse course of BD in youths (Geller et al, 2008; Kim et al, 2007; Siegel et al, 2015; Sullivan et al, 2012) and adults (Kim and Miklowitz, 2004; O’Connell et al, 1991; Yan et al, 2004), and influence psychosocial treatment outcomes (MacPherson et al, 2016; Mendenhall et al, 2009; Miklowitz et al, 2009; Reinares et al, 2016b; Sullivan et al, 2012; Weinstein et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings add to the literature on familial processes in childhood-onset BD and suggest that family functioning deficits are robust and salient into young adulthood (Belardinelli et al, 2008; Keenan-Miller et al, 2012; Nader et al, 2013; Perez Algorta et al, 2017; Schenkel et al, 2008). This is important and concerning, as family factors are associated with onset and worse course of BD in youths (Geller et al, 2008; Kim et al, 2007; Siegel et al, 2015; Sullivan et al, 2012) and adults (Kim and Miklowitz, 2004; O’Connell et al, 1991; Yan et al, 2004), and influence psychosocial treatment outcomes (MacPherson et al, 2016; Mendenhall et al, 2009; Miklowitz et al, 2009; Reinares et al, 2016b; Sullivan et al, 2012; Weinstein et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to healthy controls (HCs) and youths with other psychiatric conditions, families of youths with BD display high levels of conflict, control, aggression, quarreling, forceful punishment, tension, stress, and negative expressed emotion; and low levels of warmth, affection, intimacy, cohesion, expressiveness, organization, and positive expressed emotion (Belardinelli et al, 2008; Keenan-Miller et al, 2012; Nader et al, 2013; Perez Algorta et al, 2017; Schenkel et al, 2008). Family dysfunction also predicts worse course of BD in youths, including: 1) low maternal warmth (Geller et al, 2008); 2) chronic stress in family, romantic, and peer relationships (Kim et al, 2007; Siegel et al, 2015); 3) frequency and severity of stressful life events (Kim et al, 2007); 4) low levels of cohesion and adaptability (Sullivan et al, 2012); and 5) high levels of conflict (Sullivan et al, 2012). This relationship is also bidirectional, with patients’ symptoms/behaviors reciprocally influencing caregivers’ burden/distress (Reinares et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These predictors have previously been established in the literature as associated with impairment in BD youth (Axelson et al, 2006;Birmaher et al, 2009;Birmaher et al, 2006;Birmaher et al, 2014;Goldstein et al, 2008;Goldstein et al, 2013;Goldstein et al, 2005;Romero et al, 2009a;Romero et al, 2009b;Sala et al, 2010;Sala et al, 2012;Sala et al, 2014 We conducted Analysis of Variance (ANOVA) (Fisher, 1921) to determine whether psychosocial functioning scores (C-GAS/GAF) averaged over follow-up differed by the four Classes. We had highlighted several sociodemographic variables that had been previously identified in COBY (Birmaher et al, 2014;Goldstein et al, 2009;Siegel et al, 2015) and other studies (Biffin et al, 2009;Forcada et al, 2011;Judd et al, 2005;Martino et al, 2017;Sbrana et al, 2007;Wilens et al, 2014) as significant predictors of clinical outcomes, and subsequently tested them in a series of univariate analyses. Variables that were significant in predicting fair/poor functioning (C-GAS/GAF < 70), including age of BD onset, IQ, and family history of substance use disorder (SUD), were subsequently incorporated into the ANOVA models as covariates.…”
Section: Demographic and Clinical Assessmentsmentioning
confidence: 99%
“…These families also demonstrate low levels of: warmth, affection, and intimacy (Schenkel et al, 2008); cohesion (Belardinelli et al, 2008; Chang et al, 2001; Ferreira et al, 2013; Nader et al, 2013); expressiveness (Barron et al, 2014; Belardinelli et al, 2008); organization (Barron et al, 2014; Belardinelli et al, 2008; Chang et al, 2001; Ferreira et al, 2013; Nader et al, 2013); intellectual-cultural orientation (Barron et al, 2014; Belardinelli et al, 2008; Ferreira et al, 2013); active-recreational orientation (Barron et al, 2014; Belardinelli et al, 2008; Ferreira et al, 2013); moral-religious emphasis (Ferreira et al, 2013); and positive expressed emotion (Nader et al, 2013). In addition, worse longitudinal course of BPSD is predicted by impaired family characteristics, such as: low maternal warmth (Geller et al, 2008); chronic stress in family, romantic, and peer relationships (Kim, Miklowitz, Biuckians, & Mullen, 2007; Siegel et al, 2015); frequency and severity of independent family stressful life events (Kim et al, 2007); low levels of cohesion and adaptability (Sullivan, Judd, Axelson, & Miklowitz, 2012); and high levels of conflict (Sullivan et al, 2012). Interestingly, one study found a small but significant indirect pathway from parental mood disorder to childhood BPSD via increased family conflict (Du Rocher Schudlich, Youngstrom, Calabrese, & Findling, 2008).…”
Section: Families Of Children With Bpsdmentioning
confidence: 99%